The The Role of Nurses in Managing Anxiety Levels of Patients with HIV/AIDS: A Phenomenological Study - Nasrianti Nasrianti; Fatiah Fahri Inayati Said; Fenska Narly Makualaina; Viere Allanled Siauta; Hasnia HAsnia (GLOBAL HEALTH SCIENCE GROUP, 2025)
This study aims to explore the role of nurses in managing anxiety levels in patients with HIV/AIDS: Phenomenological Study in Papua Province. The method used is an exploratory phenomenology approach , data collection with in-depth interviews , determination of participants in this study is purposive sampling . Participants in this study were nurses who treat patients with HIV/AIDS, with the number of participants in this study as many as 3 participants. The results of the study obtained 3 themes, namely anxiety, support from those closest to them, the experience of health workers in providing services. The conclusion of the results of the study obtained 3 themes, namely anxiety, support from family and the experience of health workers. Statements from participants based on the experience of health workers in handling patients with HIV/AIDS that special attention is needed for HIV/AIDS sufferers, especially in terms of carrying out control and consuming drugs.